Electrophysiology of Error Processing : Associations With Depression, Anxiety, Fear of Failure, and Clinical Perfectionism - Leland, David S.; Moe, Simon M.; LeBouton, Gabrielle M.; Dubiel, Sean W.; Reimer, Sean W.; Dortch, Sierra D.; Beard, Katie L.; Brandt, Lucas J.; Becker, Samuel J. (My University, 2018)
One current debate about the ERN and Pe is whether they reflect performance monitoring or emotional response to errors. We predicted that ERN and Pe would correlate with depression, anxiety, fear of failure, and/or clinical perfectionism.We also looked for potential associations between ERN/Pe, self-compassion, and achievement goals.
Color poster with text, graphs, and charts.
Keywords: Posters; Electrophysiology; Mental health; Psychology; EEGs